The Motif of 76KRKCSK in Bm65 Is an Efficient Nuclear Localization Signal Involved in Production of Infectious Virions - Li, Guohui; Qi, Xinyu; Chen, Huiqing; Hu, Zhaoyang; Chen, Fangying; Deng, Liang; Guo, Zhongjian; Chen, Keping; Tang, Qi (Frontiers in Microbiology, 2019)
orf65 (Bm65) of Bombyx mori nucleopolyhedrovirus (BmNPV) codes for a putative 104-amino-acid protein containing three cysteine residues with a putative molecular mass of 12.2 kDa. Previous studies have showed that Bm65 accumulates mainly in nucleus and involved in the repair of UV-damaged DNA. However, the mechanism of nuclear import of Bm65 remains unclear. In this study, a SDS-stable Bm65 tetramer was found in BmNPV-infected BmN cells, and alanine substitutions for the three cysteine residues did not affect the formation of Bm65 tetramer. Additionally, a basic amino acid cluster of the Bm65 protein was identified as an efficient nuclear localization signal (NLS). Firstly, transient expression of GFP-fused truncated Bm65 variants revealed that the 76KRKCSK motif functions as the NLS. This was also confirmed by alanine substitution in the 76KRKCSK motif, which caused attenuated nuclear localization of Bm65. Next, the 76KRKCSK motif-mutated bacmid was generated and the 76KRKCSK motif was also found to be important for nuclear localization of Bm65 in BmNPV-infected conditions. Lastly, analyses of flag-tagged Bm65 expressing bacmids revealed that the mutations in 76KRKCSK motif did not affect the synthesis of Bm65 tetramer, but severely impaired production levels of infectious virions. In conclusion, Bm65 exists in mainly a tetrameric form in virus-infected cells, which may be involved with production levels of infectious virions.